Bleeding Disorder with Abnormal Wound Healing, Acid-Soluble Clots and Normal Factor XIII - Ragaz, Stefan; Kemp, Graham; Furlan, Miha; Beck, Eugene A. (Thrombosis and Haemostasis, 1976)
An unusual bleeding disorder clinically resembling factor XIII deficiency is presented. The only detectable coagulation abnormality was rapid clot dissolution in 1% monochloroacetic acid. This abnormality was ascribed to the sustained increase of a pepsin-like plasma protease which is activated at low pH. A systematic search for similar phenomena revealed that massive blood transfusion may also enhance plasma-clot solubility in acid, possibly by release of a red cell protease. We conclude that the acid clot solubility test is not a specific indicator of factor XIII deficiency, but this simple assay is recommended for further studies of acid plasma protease activity. The diagnostic relevance and pathophysiologic importance of increased pepsin-like activity in plasma remain to be elucidated.